Simulasi Sistem Dinamik Pada Air Minum Dalam Kemasan Cup di Perusahaan Tirta Sasmita - Maulana, Yudi; Taufik, Taufik (Jurnal Optimalisasi, 2024)
The industry is experiencing rapid growth, as evidenced by the many new companies emerging. To remain competitive, companies must have a strong strategy. Tirta Sasmita Company, an integrated company with Pamulang University, which focuses on the production of Bottled Drinking Water (AMDK), faces fluctuations in the production of AMDK cups every month. Data shows an average production output of 8,430 units, with an average fluctuation of 8.33% every month in 2022. This study aims to understand the dynamic behavior of AMDK cup production and the factors that influence it. In the simulation using Anylogic 8.8. In general, the stages of solving problems using the dynamic system method are formulating the problem, identifying existing data in the production system, processing the data obtained, formulating the model mathematically, simulating the model that has been designed and obtaining results from the simulation. The results of the research show that the simulation shows that the increase in sales by implementing the optimistic scenario is quite significant, namely, in 2027 the average sales will increase by 120,892 cups or 2,518 cartons every month. Factors that influence each other in the production of AMDK cups include raw materials, production processes and sales. Therefore, the optimistic scenario is worth considering as it promises higher sales projections